Utilization of Moodle-Based Learning Management System in Pancasila and Citizenship Education Subjects at SMK Nusantara 1 Tangerang City - Siti Nur Azizah; Damanhuri Damanhuri; Febrian Alwan Bahrudin (JED (Jurnal Etika Demokrasi), 2022)
The rapid advancement of information and communication technology has caused various educational institutions to use e-learning systems to increase the flexibility and effectiveness of learning. One of them is utilizing the Learning Management System in learning. This study aims to find out the use of the Moodle-based Learning Management System in Pancasila and Citizenship Education (PPKn) subjects at SMK Nusantara 1 Tangerang City starting from planning, implementation and evaluation, along with obstacles and solutions. This research applies a qualitative approach with a descriptive method. Data collection was carried out using observation, interviews and documentation. The results of the study found that the moodle-based Learning Management System had been put to good use in Civics subjects as a learning support medium. PPKn subject teachers have been provided with training on the use of the Learning Management System and are accustomed to using the Learning Management System in learning so that students are given convenience in the learning process because the material can be accessed easily. Obstacles faced in the use of the Learning Management System, namely the internet network, problematic systems, besides that some students are not too focused on learning. The solutions for overcoming obstacles in the use of the Learning Management system in PPKn subjects are: taking into account 1) Planning and Policy; 2) leadership; 3) infrastructure and resources; 4) Management; 5) teaching abilities and competencies of teachers; and 6) level of technical support.